Commentary: Why Has Uptake of Pneumococcal Vaccines for Children Been So Slow? The Perils of Undervaluation. Issue 2 (February 2020) - Bloom, David E.; Kirby, Paige N.; Pugh, Sarah; Stawasz, Andrew
Abstract : Pediatric pneumococcal disease exacts a substantial burden on global health, much of which is vaccine-preventable. Despite this considerable burden and the demonstrably high efficacy of pneumococcal conjugate vaccines (PCVs), the overall level of PCV uptake remains concerningly low, especially compared with that of other childhood-recommended vaccines, such as tuberculosis and polio. A broad set of plausible explanations exists for this low uptake, including logistical challenges, psychosocial factors and affordability. One additional and systematic cause of low uptake, which is the focus of our discussion, is economists' and policymakers' tendency to undervalue vaccination in general by adopting a narrow health sector perspective when performing economic evaluations of vaccines. We present an alternative, societal framework for economic evaluations that encompasses a broader set of socioeconomic benefits in addition to health benefits. Quantifying a more comprehensive taxonomy of PCV's benefits will help to address potential undervaluation and may be sufficient not only to justify recommendation and reimbursement but also to stimulate efforts and investment toward closing coverage gaps.